The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.2196/18417
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Information Related to Drug Safety Surveillance From Electronic Health Record Notes: Joint Modeling of Entities and Relations Using Knowledge-Aware Neural Attentive Models

Abstract: Background An adverse drug event (ADE) is commonly defined as “an injury resulting from medical intervention related to a drug.” Providing information related to ADEs and alerting caregivers at the point of care can reduce the risk of prescription and diagnostic errors and improve health outcomes. ADEs captured in structured data in electronic health records (EHRs) as either coded problems or allergies are often incomplete, leading to underrep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 80 publications
0
12
0
Order By: Relevance
“…A total of seven (24.1%) of the studies wrote about participation in the 2018 n2c2 challenge [ 34 , 43 , 44 , 48 , 53 , 56 , 57 ] and four (13.8%) described participation in the MADE 1.0 challenge [ 49 , 54 , 56 , 58 ] (see glossary). A further three studies (10.3%) did not participate in either challenge but used one or both of these challenge datasets [ 45 , 50 , 59 ]. Table 3 provides details on the datasets used in the studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of seven (24.1%) of the studies wrote about participation in the 2018 n2c2 challenge [ 34 , 43 , 44 , 48 , 53 , 56 , 57 ] and four (13.8%) described participation in the MADE 1.0 challenge [ 49 , 54 , 56 , 58 ] (see glossary). A further three studies (10.3%) did not participate in either challenge but used one or both of these challenge datasets [ 45 , 50 , 59 ]. Table 3 provides details on the datasets used in the studies.…”
Section: Resultsmentioning
confidence: 99%
“…Some commented on difficulties encountered when applying off-the-shelf generic pre-processing tools to clinical text. Dandala et al observed that sentence boundary detection and tokenization are difficult issues in clinical text as sentence ends are frequently denoted by newline characters rather than punctuation [ 45 ]. This was echoed in another paper where it was noted that several generic sentence segmentation tools did not perform well due to differences in punctuation patterns and the use of newline characters in formatting [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have listed the top performing methods from the 2018 n2c2 ADE challenge in Table 1. Dandala et al (2020) custom-trained biomedical ELMo embeddings using the MIMIC-III data-set (Johnson et al, 2016); they also used a rich set of sentence tokenization rules. Ju et al (2020) leveraged a tree-architecture to detect overlapping spans in addition to lexical and knowledge features (e.g., word shapes, Human Disease Ontology / MedDRA side-effect database information).…”
Section: Related Workmentioning
confidence: 99%
“…Among medication entities, ADE and Reason are challenging to disambiguate (Henry et al, 2020). Frequently, the specific reason for drug administration may appear in a subsequent sentence (Dandala et al, 2020). Besides, ADE data-sets include goldannotations for these entities, only if they are associated with a drug.…”
Section: Introductionmentioning
confidence: 99%